ANALYSIS OF LEARNING ASSESSMENT SUITABILITY WITH LEARNING OUTCOMES IN THE IMPLEMENTATION OF OUTCOME-BASED EDUCATION (OBE) CURRICULUM - Zulfikar Ali Buto Siregar; Abdul Kadir Kadir; Muhibbudin Muhibbudin Muhibbudin; Rauzatul Jannah Jannah (Universitas Labuhanbatu, 2026)
Purpose – Outcome-Based Education (OBE) is now a key component of the Merdeka Curriculum in Indonesian universities. However, in religious colleges, learning goals often do not match how students are tested. This study examines how well Course Learning Outcomes (CPMK), their indicators, and assessment methods align. It also identifies specific challenges lecturers face.Methodology – This study used a range of methods, including reviewing curriculum documents, conducting surveys, and conducting interviews. The participants were 52 lecturers from IAIN Lhokseumawe, covering different study programs with OBE-based curricula. The study analyzed data to assess how well assessments aligned with OBE goals. It also looked at common problems in implementing OBE.Findings – The results show that while Graduate Learning Outcomes (CPL) and CPMK mostly align, the assessment methods are inconsistent. There are issues with rubric consistency, assessment variety, and the use of real-world assessments that align with learning goals. Statistical analysis found a strong positive association between assessment alignment and achievement of OBE outcomes, highlighting the importance of good assessment design.Contribution – This study provides new insights into the assessment of OBE in Islamic higher education. It points out specific challenges different from those in general higher education. Although the study focuses on one institution, it highlights the need for specialized training, particularly in understanding assessments and using digital tools, to improve OBE implementation.